2012
DOI: 10.3402/ijch.v71i0.19107
|View full text |Cite
|
Sign up to set email alerts
|

Explaining reduction of pedestrian–motor vehicle crashes in Arkhangelsk, Russia, in 2005–2010

Abstract: ObjectiveTo explain a reduction in pedestrian–motor vehicle crashes in Arkhangelsk, Russia, in 2005–2010. Study designRetrospective ecological study.MethodsFor 2005–2010, police data on pedestrian–motor vehicle crashes, traffic violations, and total motor vehicles (MVs) were combined with data on changes in national road traffic legislation and municipal road infrastructure. Negative binomial regression was used to investigate trends in monthly rates of pedestrian–motor vehicle crashes per total MVs and estima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 12 publications
1
11
1
Order By: Relevance
“…33 , 34 This troubling trend reaffirms that remedial actions ought to be geared towards improving legislative, infrastructure (eg, traffic separation and calming, signalized and zebra pedestrian crossing), education, and public awareness-raising interventions with a greater focus on young road users. 9 , 13 , 15 , 35 While graduated licensing schemes may also provide an efficient avenue towards the prevention of risky road use and fatal or severe traffic crashes in young adults, 27 , 28 , 35 it seems critical the seat-belt law in Georgia to cover not only front but also rear seat occupants, with a potential to reduce fatal injuries by up to 25% when combined with strong and sustained enforcement. 1 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…33 , 34 This troubling trend reaffirms that remedial actions ought to be geared towards improving legislative, infrastructure (eg, traffic separation and calming, signalized and zebra pedestrian crossing), education, and public awareness-raising interventions with a greater focus on young road users. 9 , 13 , 15 , 35 While graduated licensing schemes may also provide an efficient avenue towards the prevention of risky road use and fatal or severe traffic crashes in young adults, 27 , 28 , 35 it seems critical the seat-belt law in Georgia to cover not only front but also rear seat occupants, with a potential to reduce fatal injuries by up to 25% when combined with strong and sustained enforcement. 1 , 19 …”
Section: Discussionmentioning
confidence: 99%
“…Number of vehicles per head population was lowest in Russia at 0.35, but one of the highest incidences of PTI was reported from a centre in Russia. The study authors suggested that this could be due to a higher proportion of pedestrians than in other populations with 52% of all road traffic injuries in the study being of a pedestrian 9 .…”
Section: Conflict Of Interest Statementmentioning
confidence: 82%
“…First, more vehicles may increase the density of traffic flow and road congestion can decrease the speed of vehicle movement and reduce severity of crashes. Second, greater density can sometimes be simultaneous with improvements in infrastructure and enforcement, as was seen in one study in Arkhangelsk area of Russia during 2006–2010 (Kudryavtsev et al 2012 ). Third, more vehicles might signify an overall switch to safer transport modes, such as using cars with improved safety measures or moving away from two wheelers to private cars induced by the motorization process (Bhalla et al 2007 ), or by a fewer non-motorized travelers (especially pedestrians) (Paulozzi et al 2007 ), or by higher proportion of vehicles with better safety features.…”
Section: Discussionmentioning
confidence: 95%
“…The Russian government has raised the priority of road safety domestically and also endorsed international actions for road safety (Medvedev 2011 ). While more regulatory efforts have been directed towards reducing road traffic injuries and fatalities and controlling risk factors, such as the Federal Target Road Safety Program (2006–2012) (Breen et al 2011 ), few studies have evaluated the effect of these social programs (Kudryavtsev et al 2012 ; Pridemore et al 2013 ). It is also important to note that there are no studies, which describe RTF trends at sub-national level or the relationship between economic development and RTFs in Russia.…”
Section: Introductionmentioning
confidence: 99%